Persistent hiccups following thalamic hemorrhage: A case report - Vikram Shivkumar; Dipali Nemade; Neelu Dhingra (Heliyon, 2023)
Persistent hiccups (lasting more than 48 hours) can cause physical and emotional distress. They can result in dehydration, exhaustion, malnutrition, insomnia, wound dehiscence, ventilatory desynchronization, and hemodynamic changes. Hiccups are thought to be due to a complex reflex arc involving peripheral nerves and central structures such as the brainstem, temporal lobe, basal ganglia, hypothalamus, and spinal cord levels C3-5. Medullary strokes, for instance, have been reported to cause hiccups. We report a patient with a thalamic bleed who developed persistent hiccups. A 56-year-old man was brought to the hospital in an unresponsive state. He was intubated for airway protection. CT brain showed a left thalamic hemorrhage with edema and mass effect on the 3rd ventricle, intraventricular extension of hemorrhage, and hydrocephalus. An external ventricular drain was placed successfully with adequate drainage. One week after admission, the patient developed persistent abdominal jerks. These jerks were occurring every 3–4 seconds and would last for hours with brief periods of remission. He was started on levetiracetam 1000 mg IV bid and then increased to 1500 mg IV BID without any improvement of symptoms. The patient was also placed on EEG which did not reveal any epileptiform abnormality but did show an EMG artifact. His electrolytes including sodium, and potassium, and corrected calcium levels were normal. He did not have any evidence of pneumonia or other infections. It was determined that these jerks were likely hiccups. Metoclopramide 10 mg IV was tried without any benefit. He was then started on Baclofen 10 mg PO TID which resulted in a significant improvement in hiccups. Our case suggests that thalamic lesions might also lead to persistent hiccups.